Transporte aéreo no Brasil: a dinâmica dos fluxos turísticos por voos regulares, charter e fretamentos domésticos de passageiros. - - Aredes, Airton [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The purpose of this research was a reflection on the flows produced by spatial interactions resulting from the relationship between air transport and tourism, the bias of the charter and domestic passenger charter. In our perspective, we believe that these flights did not initially have a close relationship with regular passenger flows of tourists resulting spatial interactions between the living spaces and work and leisure and tourism. At this stage of society is undeniable that the influence of the scientific-technical and informational spatial organization, the speed in shifts, as well as the realization of capital is critical in that the distances between the completion of the work and tourism are increasing, but more facilitated by the use of modal shifts in air space. Whether business or leisure and tourism the air mode is configured as an important means for intensifying territorial fluidity and sent us to reflect on the origin of this invention and their innovations over time. Thus, we describe how was the development of air transport in Brazil and worldwide basing ourselves in a historical approach and linking it to the development of tourism. Then, we focus on how the technical-scientific-informational prevailed in organizing the aerial dimension of geographic space, seen by us as a system of objects, actions and norms that has repercussions on flights not scheduled (charter). Then we discuss the relationship between tourism and air transport by initially scheduled and further by regular flights not seeking to demonstrate its evolution ... (Complete abstract click electronic access below)

A presente pesquisa teve por propósito uma reflexão sobre os fluxos produzidos pelas interações espaciais resultantes da relação entre transporte aéreo e turismo, pelo viés dos voos charter e de fretamentos domésticos de passageiros. Em nossa perspectiva, consideramos inicialmente que esses voos não regulares têm estreita relação com os fluxos de passageiros turistas resultantes das interações espaciais entre os espaços de vivência e trabalho e os espaços de lazer e turismo. No atual estágio da sociedade em que é inegável a influência do meio técnico-científico-informacional na organização espacial, a velocidade nos deslocamentos, assim como a de realização do capital é fundamental na medida em que as distâncias entre a realização do trabalho e do turismo estão cada vez maiores, porém, mais facilitadas pela utilização do modal aéreo nos deslocamentos espaciais. Seja a trabalho ou a lazer e turismo o modal aéreo se configura como importante meio para intensificação da fluidez territorial e remeteu-nos a refletir sobre a origem dessa invenção e suas inovações ao longo do tempo. Dessa forma, procuramos descrever como se deu o desenvolvimento do transporte aéreo no mundo e no Brasil baseando-nos em uma abordagem histórica e relacionando-o com o desenvolvimento do turismo. Em seguida, procuramos enfocar como o meio técnico-científico-informacional se impôs na organização da dimensão aérea do espaço geográfico, visto por nós como um sistema de objetos, ações e normas que tem reflexos nos voos não regulares (charter e fretamentos) ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Air transport; Spatial interactions; Flows; Tourism; Geografia; Aeronautica comercial; Espaço aereo; Trânsito - Fluxo; Turismo; Geography